Treatment and prevention of acute and recurrent ankle sprain: an overview of systematic reviews with meta-analysis - Doherty, C.; Bleakley, C.; Delahunt, E.; Holden, S. (British Journal of Sports Medicine, 2017)
Background: Ankle sprains are highly prevalent with high risk of recurrence. Consequently, there are a significant number of research reports examining strategies for treating and preventing acute and recurrent sprains (otherwise known as chronic ankle instability (CAI)), with a coinciding proliferation of review articles summarising these reports.